Regional Centers of Islamic Learning and the Construction of Juristic Thought: Methodological Contributions of Jamia Faridia Sahiwal and Allama Abu al-Nasr Manzoor Ahmad Shah: مقامی علمی مراکز کا فقہی فکر کی تشکیل میں کردار: جامعہ فریدیہ ساہیوال اور علامہ ابو النصر منظور احمد شاہ کی منہجی خدمات کا مطالعہ - Muhammad Ameen, Muhammad Ameen; Dr. Muhammad Shahid , Dr. Muhammad Shahid (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Allama Abu al-Nasr Manzoor Ahmad Shah (1930–2019): Life, Scholarship, and Religious Legacy. Allama Abu al-Nasr Manzoor Ahmad Shah (رحمہ اللہ), famously known by the title Fateh-e-Isaiyat (Conqueror of Christianity), was born on 13 December 1930 in Pir Bakhsh Chauhan, District Ferozepur, British India. His lineage traces back through forty generations to Hazrat Muslim bin Aqeel (رضی اللہ عنہ), the nephew of Hazrat Ali (کرم اللہ وجہہ) and cousin of Imam Husayn (رضی اللہ عنہ), which establishes his Hashemite descent. His birth, according to family tradition, was foretold by Hazrat Shaykh Abdul Qadir Jilani (رحمہ اللہ). He acquired his formal religious education at Jamia Hanafia Faridia, Basirpur, where between 1948 and 1950 he mastered the classical Dars-e-Nizami curriculum, excelled in the traditional Islamic sciences, and completed Dawrah-e-Hadith, earning his sanad of graduation. On the instruction of his teacher, Mufti Noorullah Naeemi (رحمہ اللہ), he assumed teaching responsibilities in Sahiwal. Recognizing his intellectual capacity, the Government of Pakistan selected him among twenty-five scholars for advanced training at the Ulama Training Academy in Quetta, from where he received a distinction certificate in 1962, followed by further certification from the Peshawar Academy in 1964. Seeking higher scholarly refinement, he studied for two years at Jamia Islamia Bahawalpur under the renowned Allama Syed Ahmad Saeed Shah Kazmi (رحمہ اللہ). ۔ In 1964, he laid the foundation of Jamia Faridia Sahiwal, which became a prominent center of Islamic learning. Until his passing in 2019, he devoted his entire life to teaching, research, authorship, and religious preaching. Through continuous instruction and spiritual guidance, he trained countless students. Today, thousands of his disciples are actively engaged in teaching and religious services across Pakistan and abroad. Allama Manzoor Ahmad Shah passed away on 25 August 2019 (24 Dhul-Hijjah 1440 AH) at the age of 89. His funeral, one of the largest in Sahiwal’s history, was led by his son, Professor Dr. Mufti Muhammad Mazhar Farid Shah. He authored over 150 works, including Tafsir Noor-ul-Qur’an and Jalwa-e-Janan, leaving a lasting scholarly and missionary legacy.